Impact of PCB layout design on final product's EMI compliance - None Kye Yak See; M. Oswal; W. Khan-ngern; F. Canavero; C. Christopoulos; H. Grabinski (My University, 2006)
Most design engineers still believe that with a good shielded enclosure, well-shielded cables and high-performance ferrite sleeves, EMI compliance will be a straight forward task. This paper demonstrates experimentally that a poor PCB layout can cause electronic product to fail EMI specification badly even with all these fixes.
Keywords: Shielded cable; Enclosure; Electromagnetic Compatibility; Electromagnetic Compatibility and Noise Suppression